EDUCATION OF Qur'anic Morals IN SURAH MADANIYAH: A COMPARATIVE STUDY OF THE INTERPRETATIONS OF AL-TABARI AND AL-QURTUBI - Muhammad Hamdani; Mesran Mesran (Jurnal Bilqolam Pendidikan Islam, 2026)
This study examines the concept of moral education in the Qur’an through a comparative analysis of the classical exegeses of Al-Tabari and Al-Qurtubi on Surahs Al-Baqarah, Ali Imran, An-Nisa, and Al-Ma’idah. The increasing concern over ethical degradation and character formation in contemporary Muslim societies highlights the importance of revisiting Qur’anic moral teachings within authoritative classical tafsir traditions. The study aims to identify the ethical values embedded in the selected surahs and analyze the methodological distinctions between Al-Tabari’s narrational approach and Al-Qurtubi’s legal-social interpretation in constructing Qur’anic moral education. This research employs a qualitative library-based design using thematic and comparative methods of Qur’anic exegesis. Primary sources include Jāmi‘ al-Bayān by Al-Tabari and Al-Jāmi‘ li Ahkām al-Qur’ān by Al-Qurtubi, supported by contemporary scholarship on Islamic education and Qur’anic ethics. The findings demonstrate that moral education in the selected surahs encompasses spiritual integrity, social responsibility, justice, tolerance, communal ethics, and accountability. Al-Tabari predominantly emphasizes transmitted narrations and textual authority, whereas Al-Qurtubi develops a more contextual and practical ethical framework grounded in legal and social considerations. The study contributes to contemporary Islamic moral education discourse by integrating classical Qur’anic exegesis with modern character education perspectives, thereby reaffirming the continuing relevance of classical tafsir in addressing present ethical and educational challenges.